Assessing the Potential of a Formalin‐Killed Cells (FKC) Vaccine Against Edwardsiella anguillarum in Milkfish ( Chanos chanos ) - Atiek Rahmawaty; Li‐Wu Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2026)
Edwardsiella anguillarum causes Edwardsiellosis in fish, resulting in severe internal organ lesions and substantial economic losses in aquaculture. The limited efficacy of antibiotics in treating this disease, coupled with concerns regarding resistance and side effects, has driven interest in exploring fish vaccines. Various vaccine candidates derived from E. anguillarum, including inactivated cells and protein subunits, have shown potential. Here, we developed a vaccine against E. anguillarum in milkfish, and its efficacy was evaluated through vaccination challenge trials using milkfish as the target species. The formalin‐killed vaccine (FKC) in combination with an adjuvant exhibited superior efficacy, achieving a relative percent survival (RPS) of 83.4%. Furthermore, the agglutination titers indicated a robust immune response in the FKC + Adjuvant group, suggesting a potent and sustained antibody response. Additionally, serum lysozyme activity was significantly higher in vaccinated fish than in controls. Immune‐related gene expression analysis in spleen and head kidney revealed that IL‐1β peaked at 14 days post‐vaccination, indicating early pro‐inflammatory response, while MHC‐II showed progressive elevation, suggesting sustained antigen presentation and humoral immunity. Overall, this study underscores the effectiveness of the FKC + Adjuvant combination in enhancing immune response and protecting against bacterial pathogens in aquaculture, presenting a promising strategy for disease control.